Physical Education Teachers' Perceptions of Inclusive Learning in Elementary Schools, Martapura District - Azizah, Rahma; Rahmadi, Rahmadi; Haffyandi, Recky Ahmad (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to explore the perceptions of Physical Education (PE) teachers toward inclusive learning in elementary schools within Martapura District. Employing a quantitative descriptive method, data were gathered through a 4-point Likert scale questionnaire distributed to 13 PE teachers selected purposively from 7 elementary schools. Participants were chosen based on having a minimum of one year of experience in teaching inclusive classes. The total population encompassed 39 elementary schools in the district. The results revealed a limited understanding of inclusive education among teachers, with 38% indicating inadequate knowledge of its concepts. Similarly, 38% of the respondents fell into the low category in terms of readiness and ability to deliver inclusive Physical Education. A significant proportion of teachers (77%) reported encountering substantial barriers in implementing inclusive learning, such as insufficient training, lack of supporting facilities, and the absence of specialised co-teachers. Despite these challenges, the study found that institutional support—particularly from school principals and inclusive-oriented policies—was relatively strong, with 46% of respondents reporting a high level of school-based backing, albeit with variations across institutions. These findings suggest that while policy-level support exists, the implementation of inclusive PE remains inconsistent and underdeveloped. The study concludes that enhancing inclusive Physical Education requires targeted teacher training programs, better infrastructural support, and stronger collaboration among educators, administrators, and policymakers. Strengthening these components is essential to realise the full potential of inclusive education in fostering equal participation for all students in Physical Education settings.